Intraspecific variation within the utricularia amethystina species morphotypes based on chloroplast genomes - Silva, Saura R. [UNESP]; Pinheiro, Daniel G. [UNESP]; Penha, Helen A. [UNESP]; Płachno, Bartosz J.; Michael, Todd P.; Meer, Elliott J.; Miranda, Vitor F. O. [UNESP]; Varani, Alessandro M. [UNESP] (MDPI, 2019)
Utricularia amethystina Salzm. ex A.St.-Hil. & Girard (Lentibulariaceae) is a highly polymorphic carnivorous plant taxonomically rearranged many times throughout history. Herein, the complete chloroplast genomes (cpDNA) of three U. amethystina morphotypes: purple-, white-, and yellow-flowered, were sequenced, compared, and putative markers for systematic, populations, and evolutionary studies were uncovered. In addition, RNA-Seq and RNA-editing analysis were employed for functional cpDNA evaluation. The cpDNA of three U. amethystina morphotypes exhibits typical quadripartite structure. Fine-grained sequence comparison revealed a high degree of intraspecific genetic variability in all morphotypes, including an exclusive inversion in the psbM and petN genes in U. amethystina yellow. Phylogenetic analyses indicate that U. amethystina morphotypes are monophyletic. Furthermore, in contrast to the terrestrial Utricularia reniformis cpDNA, the U. amethystina morphotypes retain all the plastid NAD(P)H-dehydrogenase (ndh) complex genes. This observation supports the hypothesis that the ndhs in terrestrial Utricularia were independently lost and regained, also suggesting that different habitats (aquatic and terrestrial) are not related to the absence of Utricularia ndhs gene repertoire as previously assumed. Moreover, RNA-Seq analyses recovered similar patterns, including nonsynonymous RNA-editing sites (e.g., rps14 and petB). Collectively, our results bring new insights into the chloroplast genome architecture and evolution of the photosynthesis machinery in the Lentibulariaceae.
Keywords: Carnivorous plants; Chloroplast phylogenomics; Intraspecific variation; Lentibulariaceae; Ndh genes; Organelle genome; Polymorphic species; Utricularia amethystina